Adoptive cell therapy for acute myeloid leukemia. Issue 6 (12th May 2019) - Ma, Hongbing; Padmanabhan Iyer, Swaminathan; Parmar, Simrit; Gong, Yuping
Abstract: Acute myeloid leukemia (AML) is the most common tumor in adult patients, most of the patients have a poor prognosis even after high-intensity chemotherapy, especially for relapsed, refractory or elderly patients. Therefore, new methods are needed to change the outcomes. In recent years, an increasing number of immune-therapies are emerging where adoptive cell therapy, a special immunotherapy, has become a promising strategy for AML. Here, we review the clinical application and advancement of donor lymphocyte infusion, chimeric-antigen receptor (CAR) T cell therapy, natural killer (NK) cell therapy and dendritic cell vaccination for AML, hopefully providing an overview of clinical aspects of advances in adoptive cell therapy for AML.